Current Topics in Chirality From Chemistry to Biology - Akitsu, Takashiro (IntechOpen, 2021)
Chirality is a concept related not only to organic chemistry but also to each field of natural science. Awareness of hierarchy is important for universal and comprehensive understanding. As such, this book examines myriad subjects related to chirality in chemistry and interdisciplinary applications. In contrast to the previous book, this new book about chirality includes contributions from authors in many fields of natural science, providing a wider overview. The book's focus is chirality and organic chemistry, including synthesis and reactions.